2008
DOI: 10.1002/mc.20432
|View full text |Cite
|
Sign up to set email alerts
|

COMT polymorphisms affecting protein expression are risk factors for endometrial cancer

Abstract: In estrogen metabolic pathways, the COMT enzyme is related to detoxification. COMT gene polymorphisms have been shown to effect enzyme function. We hypothesized that these polymorphisms may be risk factors for endometrial cancer (EC). DNA samples from 150 cases of EC and healthy controls (n = 165) were analyzed by PCR-RFLP to determine the genotypic frequency of four different polymorphic loci on COMT [codon 62 (rs4633), 102 (rs5031015), 136 (rs4818), 158 (rs4680)]. Genotyping was confirmed by direct DNA seque… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(28 citation statements)
references
References 24 publications
0
28
0
Order By: Relevance
“…The AA (Met/Met) genotype of rs4680 has been shown to confer a 2-to 4-fold decrease in COMT enzyme activity. [34][35][36][37] The A allele of SNP rs4680 has also previously been associated with a poorer prognosis in Chinese women under a recessive model (HR AA vs. AG/GG 5 1.6 [95% CI:1.1-2.3, p 5 0.01]). 7 The A-allele is the minor allele in the Chinese population and the common allele in the British data set studied here (MAF 5 0.26, 0.52, respectively).…”
Section: Discussionmentioning
confidence: 99%
“…The AA (Met/Met) genotype of rs4680 has been shown to confer a 2-to 4-fold decrease in COMT enzyme activity. [34][35][36][37] The A allele of SNP rs4680 has also previously been associated with a poorer prognosis in Chinese women under a recessive model (HR AA vs. AG/GG 5 1.6 [95% CI:1.1-2.3, p 5 0.01]). 7 The A-allele is the minor allele in the Chinese population and the common allele in the British data set studied here (MAF 5 0.26, 0.52, respectively).…”
Section: Discussionmentioning
confidence: 99%
“…This change is believed to account for a three-to four-fold reduction in COMT activity (Weinshilboum and Raymond, 1977;Dawling et al, 2001). Several lines of evidence have suggested that the presence of this variant COMT could Jin-Ze Du et al increase the risk of hormonally influenced cancers because of its decreased ability to inactivate catechol estrogens and by producing intermediate products of catechol estrogen metabolism (Hirata et al, 2008;Tian et al, 2014). Therefore, it is biologically reasonable to hypothesize that individuals with the low-activity COMT-A (COMT-Met) allele are more likely to be at higher risk of ovarian cancer owing to the formation and accumulation of carcinogenic catechol estrogens.…”
Section: Introductionmentioning
confidence: 99%
“…A total of 15 studies with full-text articles examined the association of COMT Val158Met polymorphism with endometrial and ovarian cancer were found (Goodman et al, 2000;Goodman et al, 2001;Garner et al, 2002;McGrath et al, 2004;Zimarina et al, 2004;Doherty et al, 2005;Sellers et al, 2005;Tao et al, 2006;Holt et al, Szyllo et al, 2007;Zhao et al, 2007;Delort et al, 2008;Hirata et al, 2008). As summarized in (Table 1), the eligible studies were selected for this meta-analysis, including 1, 293 cases and 2, 647 controls for ovarian cancer (from eight studies) and 2, 174 cases and 2, 699 controls for endometrial cancer (from seven studies).…”
Section: Eligible Studies and Meta-analysis Databasesmentioning
confidence: 99%
“…It has been hypothesized that this COMT polymorphism (rs4680) may modulate risk of hormonally responsive cancers because of a decreased ability of COMT to methylate and thereby inactivate catechol estrogens, as well as through decreased production of the intermediate products of catechol estrogen metabolism (Lajin et al, 2013). To data, several epidemiologic studies have investigated the relationship between the COMT polymorphism and predisposition to endometrial and ovarian cancer (Goodman et al, 2000;Goodman et al, 2001;Garner et al, 2002;McGrath et al, 2004;Zimarina et al, 2004;Doherty et al, 2005;Sellers et al, 2005;Tao et al, 2006;Holt et al, 2007;Szyllo et al, 2007;Wang et al, 2007;Zhao et al, 2007;Delort et al, 2008;Hirata et al, 2008;Jakubowska et al, 2010). Although it is an appealing hypothesis that genes affecting the production or metabolism of estrogen may affect the risk of hormonally related cancers, the evidence from the literature is inconsistent.…”
Section: Introductionmentioning
confidence: 99%